Seattle Exposition March - J.A. Bennett::::::::: (Victor Kremer Co.)
Piano score, 6 p. On cover: Written for the Alaska-Yukon-Pacific Exhibition, 1909. Also on cover: Seal of the exposition in color (3-D?) ports. of exposition officials. Publishers advertisement on verso of last leaf.